Sergej : das schwule Szene Magazin. (Berlin : Sergej Medien- und Verlags-GmbH, 1997)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Kopenhagener Strasse 14, 10437 Berlin
Duits
Periodiek